Healthcare Quality Management: A Study on Quality Awareness among Employees of Indian Hospitals - Natarajan Nithya; V. P. Rameshkumar (International Journal of Supply Chain Management, 2019)
ABSTRACT The study has made an attempt to measure the effectiveness of hospital quality management practices to meet quality performance. Keeping this as an objective, the study dealt with quality awareness which may affect the quality performance of hospitals. The study was conducted among network hospitals accredited for Tamilnadu Government Employees New Health Insurance Scheme in India. Among 514 hospitals, 490 hospitals located in Tamilnadu were taken as population size and a sample of 245 hospitals were chosen for the study using systematic sampling method. The data were collected from top and middle level executives of network hospitals. The study adopted descriptive statistics, factor analysis and one-way ANOVA for its analytical process. From the findings of the study it was observed that, larger share of the respondents profile is from clinical and non-clinical departments and mostly heads of the departments represented for the survey. The study observed that the level of quality awareness among executives were moderate in nature. The study observed that the level of quality awareness among executives were moderate in nature. Further the variable, quality awareness were reduced to two factors. These factors were used for further investigation and found that respondents profile like designation, no. of years of experience and the departments are associated with many of the Quality practices. Keywords: Quality management, healthcare management, quality awareness, Indian Hospitals